MODERATION IN ISLAMIC COMMUNICATION PERSPECTIVES OF TADABBUR ALQURAN - Lubis, Muya Syaroh Iwanda; Nst, Asrindah; Sabaruddin S, Sabaruddin S (Universitas Dharmawangsa Medan, 2022)
ABSTRACTThis research was set aside in 2019 as a year of international moderation by the UN general assembly. Since then, the moderate movement particularly in Indonesia has been carried out massively throughout the realms of life. The problem is what moderates the context of islamic communication? And what about moderation in the Koran? The method is a qualitative description based on library studies with a Koran tadabbur approach. The invention is that moderation is a godlike, social responsibility, unity and universal humanity. The principle to be noted is: first, moderation must be measured and always within the circle of shalloath. Second, moderation must frame the spirit of being the best people. Third, moderation must be a central pillar supporting the civility of Islam to become the life and mercy of the human universe.Keywords: moderi, islamic communications, Koran tadabbur